Intertemporal Preferences and Labor Supply - Hotz, V. Joseph; Kydland, Finn E.; Sedlacek, Guilherme L. (Econometrica, 1988)
Recently, several authors have argued for the use for the use of dynamic preference structures for leisure which incorporate forms of intertemporally nonseparable utility in the analysis of intertemporal labor supply decisions. In this paper, we examine whether such nonseparable utility functions are important in characterizing microdata on life-cycle labor supply. Using longitudinal data on males from the Panel Study of Income Dynamics, we estimate a model of life-cycle labor supply and consumption under uncertainty in which the structure of intertemporal leisure preferences is allowed to be nonseparable in leisure. Our model nests as special cases a number of alternative specifications considered in the literature. We investigate the robustness of our findings to certain forms of population heterogeneity and to some types of model misspecification. Across a number of alternative specifications, we find evidence that the standard assumption of intertemporally separable preferences for leisure is not consistent with data for prime-age males.